Should women aged 70–74 be invited to participate in screening mammography? A report on two Australian community juries. Issue 6 (14th June 2018) - Degeling, Chris; Barratt, Alexandra; Aranda, Sanchia; Bell, Robin; Doust, Jenny; Houssami, Nehmat; Hersch, Jolyn; Sakowsky, Ruben; Entwistle, Vikki; Carter, Stacy M
Abstract : Objective: To elicit informed views from Australian women aged 70–74 regarding the acceptability of ceasing to invite women their age to participate in government-funded mammography screening (BreastScreen). Design: Two community juries held in 2017. Setting: Greater Sydney, a metropolis of 4.5 million people in New South Wales, Australia. Participants: 34 women aged 70–74 with no personal history of breast cancer, recruited by random digit dialling and previously randomly recruited list-based samples. Main outcomes and measures: Jury verdict and rationale in response to structured questions. We transcribed audio-recorded jury proceedings and identified central reasons for the jury's decision. Results: The women's average age was 71.5 years. Participants were of diverse sociocultural backgrounds, with the sample designed to include women of lower levels of educational attainment. Both juries concluded by majority verdict (16–2 and 10–6) that BreastScreen should continue to send invitations and promote screening to their age group. Reasons given for the majority position include: (1) sending the invitations shows that society still cares about older women, empowers them to access preventive health services and recognises increasing and varied life expectancy; (2) screening provides women with information that enables choice and (3) if experts cannot agree, the conservative approach is to maintain the status quo until the evidence is clear. Reasons for the minority position were the potential for harms through overdiagnosis and misallocation of scarce health resources. Conclusions: Preventive programmes such as mammography screening are likely to have significant symbolic value once they are socially embedded. Arguments for programme de-implementation emphasising declining benefit because of limited life expectancy and the risks of overdiagnosis seem unlikely to resonate with healthy older women. In situations where there is no consensus among experts on the value of established screening programmes, people may strongly prefer receiving information about their health and having the opportunity make their own choices.